Aetiology of anthracnose on grapevine shoots in Brazil. (23rd October 2017) - Santos, R. F.; Ciampi‐Guillardi, M.; Amorim, L.; Massola, N. S.; Spósito, M. B.
Abstract : Anthracnose is an important disease in vineyards in south and southeast Brazil, the main grape‐producing regions in the country. This study aimed to identify the causal agents of grapevine anthracnose in Brazil through multilocus phylogenetic analyses, morphological characterization and pathogenicity tests. Thirty‐nine Elsinoë ampelina and 13 Colletotrichum spp. isolates were obtained from leaves, stems and berries with anthracnose symptoms collected in 38 vineyards in southern and southeastern Brazil. For E. ampelina isolates, the internal transcribed spacer (ITS), histone H3 ( HIS3 ) and elongation factor 1‐α ( TEF ) sequences were analysed. HIS3 was the most informative region with 55 polymorphic sites including deletions and substitutions of bases, enabling the grouping of isolates into five haplotypes. Colonies of E. ampelina showed slow growth, variable colouration and a wrinkled texture on potato dextrose agar. Conidia were cylindrical to oblong with rounded ends, hyaline, aseptate, (3.57–) 5.64 (−6.95) μm long and (2.03–) 2.65 (−3.40) μm wide. Seven species of Colletotrichum were identified: C. siamense, C. gloeosporioides, C. fructicola, C. viniferum, C. nymphaeae, C. truncatum and C. cliviae, with a wide variation in colony and conidium morphology. Only E. ampelina caused anthracnose symptoms on leaves, tendrils and stems of Vitis vinifera and V. labrusca . High disease severity and a negative correlation between disease severity and shoot dry weight were observed only when relative humidity was above 95%. In this study, only E. ampelina caused anthracnose symptoms on grapevine shoots in Brazil.